The political philosophy of the European city from polis, through city-state, to megalopolis? - Horkay Hörcher, Ferenc (Political theory for today., 2021)
"The Political Philosophy of the European City offers a wide-ranging panorama of urban political culture in Europe. Its historical scope ranges from the ancient polis through Italian city-states to the ideal of "small is beautiful" in the 20th century. As a political theory, it offers an analysis of conservative, urban republicanism"--